2010
DOI: 10.1097/mpg.0b013e3181dac094
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endoscopic Ultrasound for Evaluating Gastrointestinal Tract Disorders in Pediatrics: A Tertiary Care Center Experience

Abstract: EUS ± FNA is feasible and safe and makes a significant impact on most pediatric patients. Nurse-administered propofol sedation appears to be safe and well tolerated in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 23 publications
2
49
0
2
Order By: Relevance
“…However, data on its safety and ability to impact clinical care among pediatric patients is limited to a few case series [Table 3]. [12345] Most of these case series are based on a small cohort of patients, but they all have uniformly suggested that EUS is safe and makes a meaningful impact on the care of pediatric patients. [125] Here, we present our experience with pediatric EUS, and our study represents one of the largest case series addressing the feasibility and the safety of EUS in pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, data on its safety and ability to impact clinical care among pediatric patients is limited to a few case series [Table 3]. [12345] Most of these case series are based on a small cohort of patients, but they all have uniformly suggested that EUS is safe and makes a meaningful impact on the care of pediatric patients. [125] Here, we present our experience with pediatric EUS, and our study represents one of the largest case series addressing the feasibility and the safety of EUS in pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…[13456] Some noticeable differences were that 14% (8/58) of our cases were for suspected insulinoma; six patients had hereditary cancer syndromes and were undergoing EUS for surveillance or for the evaluation of gastro-duodenal polyps. Although these differences are reflective of practice patterns and differences in the tertiary referral patterns, our study provides safety data on additional indications in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[123] A recent novel application in adults is EUS-guided liver biopsy (EUS-LB) which has proven to be technically safe, and provides adequate tissue yields for evaluation of liver disease;[4567] but the use of EUS-LB has never been reported in the pediatric population. We report the first case series of EUS-LB performed in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%